Progress in evaluation of cervical metastatic lymph nodes of differentiated thyroid cancer with ultrasonography - TIAN Yan, MA Jiaojiao, XI Xuehua, ZHANG Bo (Jichu yixue yu linchuang, 2023)
Accurate evaluation of cervical metastatic lymph nodes is of great significance to the risk staging, treatment and prognosis of patients with differentiated thyroid cancer(DTC). Ultrasonography is the main examination method to evaluate cervical lymph nodes. In recent years, with the emergence and extensive application of new technologies such as elastic imaging, contrast-enhanced ultrasonography, fine needle aspiration cytology and artificial intelligence, the diagnostic effectiveness of cervical metastatic lymph nodes of DTC has been further improved.